ENABLERS OF GREEN SUPPLY CHAIN MANAGEMENT AND SUSTAINABILITY PERFORMANCE - Agus, Aziz; Kusmantini, Titik; Nilmawati, Nilmawati (Faculty of Economics and Business, University of Pasundan, 2025)
This study investigates the enabling factors of Green Supply Chain Management (GSCM) practices and their impact on sustainability performance, with a particular focus on economic performance among furniture Micro, Small, and Medium Enterprises (MSMEs) in Yogyakarta. The urgency of this research lies in the inconsistent findings of previous studies regarding GSCM’s effectiveness in improving firm performance and the limited exploration of its enabling factors. Using a quantitative approach, the study surveyed 75 export-oriented furniture MSMEs, selected through purposive sampling, and analyzed the data using SmartPLS 4.0. The results show that consumer behavior and organizational strategy significantly influence GSCM adoption, while institutional pressures and economic advantages do not. GSCM practices positively influence environmental and social performance, but do not directly or indirectly improve economic performance. This study contributes to the literature by integrating both the drivers and the outcomes of GSCM in a single empirical framework specific to the MSMEs context.